Administrative (in)Visibility of Patient Structural Vulnerability and the Hierarchy of Moral Distress among Health Care Staff. (12th February 2019) - Armin, Julie S.
Abstract: Public programs such as Medicaid offer highly circumscribed access to health care for low‐income patients in the United States. This article describes the work of a variety of health care staff who manage specialized cancer care for publicly insured patients who have difficulty gaining or maintaining program eligibility or for uninsured and undocumented patients who are excluded from state programs. I highlight the moral distress that occurs when clinic employees become individually responsible for reconciling policies that limit patients' access to care. I conclude that responsibility for securing access to cancer care for structurally vulnerable patients frequently falls to safety net clinics and that patients' financial constraints are visible to particular types of staff, such as non‐licensed health care staff and non‐physician providers, who may experience moral distress disproportionately.